Maternal Lactase Polymorphism (rs4988235) Is Associated with Neural Tube Defects in Offspring in the National Birth Defects Prevention Study. Issue 2 (24th January 2019) - Hoang, Thanh T; Lei, Yunping; Mitchell, Laura E; Sharma, Shreela V; Swartz, Michael D; Waller, D Kim; Finnell, Richard H; Benjamin, Renata H; Browne, Marilyn L; Canfield, Mark A; Lupo, Philip J; McKenzie, Paige; et al.
ABSTRACT: Background: The risk of neural tube defect (NTD)–affected pregnancies is reduced with adequate folic acid intake during early pregnancy. However, NTDs have been observed among offspring of women with adequate folic acid intake. Some of these women are possibly not absorbing enough folic acid. Because lactase deficiency can lead to poor nutrient absorption, we hypothesized that lactase-deficient women will be at increased risk of having offspring with NTDs. Objective: We examined the association between maternal rs4988235 (a lactase deficiency genetic marker) and NTDs in offspring. Methods: We conducted a case-control study using data from the National Birth Defects Prevention Study, United States, 1997–2009, restricting to non-Hispanic white (NHW) and Hispanic women. Cases were women with an offspring with an NTD ( n = 378 NHW, 207 Hispanic), and controls were women with an offspring without a birth defect ( n = 461 NHW, 165 Hispanic). Analyses were conducted separately by race/ethnicity, using logistic regression. Women with the CC genotype were categorized as being lactase deficient. To assess potential effect modification, analyses were stratified by lactose intake, folic acid supplementation, dietary folate, and diet quality. Results: Among NHW women, the odds of being lactase deficient were greater among cases compared with controls (OR: 1.37; 95% CI: 1.02, 1.82). Among Hispanic women, the odds of being lactase deficient were significantly lower among cases compared with controls (OR: 0.50, 95% CI: 0.33, 0.77). The association differed when stratified by lactose intake in NHW women (higher odds among women who consumed ≥12 g lactose/1000 kcal) and by dietary folate in Hispanic women (opposite direction of associations). The association did not differ when stratified by folic acid supplementation or diet quality. Conclusions: Our findings suggest that maternal lactase deficiency is associated with NTDs in offspring. However, we observed opposite directions of effect by race/ethnicity that could not be definitively explained.